2021
DOI: 10.3390/nu13031006
|View full text |Cite
|
Sign up to set email alerts
|

Protein Knowledge of Older Adults and Identification of Subgroups with Poor Knowledge

Abstract: The aim was to investigate the protein knowledge of community-dwelling older adults. A survey was conducted among 1825 adults aged ≥65 years and living in Finland, Netherlands, Poland, Spain and United Kingdom in 2017. Protein knowledge was measured with nine objective knowledge statements provided only to participants who indicated to know what the nutrient "protein" is (64.7% of sample). Demographic, socioeconomic and health determinants of poor protein knowledge were investigated using multiple logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…However, the concern was expressed that many women would be unable to identify clearly low or high protein foods, suggesting the need for targeted education. This advice is consistent with the outcomes of a recent large study on ‘Protein Knowledge’ among older women and men 57 . Given the precise nature of the quantitative changes required in protein intake, this warrants particular attention.…”
Section: Discussion With Consumerssupporting
confidence: 79%
“…However, the concern was expressed that many women would be unable to identify clearly low or high protein foods, suggesting the need for targeted education. This advice is consistent with the outcomes of a recent large study on ‘Protein Knowledge’ among older women and men 57 . Given the precise nature of the quantitative changes required in protein intake, this warrants particular attention.…”
Section: Discussion With Consumerssupporting
confidence: 79%
“…About half of community‐dwelling older adults have poor protein knowledge, 24 which was experienced in our study sample as well. Without increasing knowledge of the importance of protein, the most vulnerable older individuals will be at risk of malnutrition and frailty.…”
Section: Discussionmentioning
confidence: 72%
“…Although not directly investigating protein for exercise recovery, a recent study has also found poor knowledge of dietary protein amongst 1,825 community-dwelling European older adults. Using an online survey, it was determined that 35.3% of the sample did not know what dietary protein was, and low protein knowledge was observed in 902 (49.4%) participants of the total study sample ( 18 ). Of more relevance to the current study is that amongst individuals with low protein knowledge, only 65% responded correctly to the statement that “You need protein in the diet for repairing bones and muscles.” Similarly, a recent feasibility study has shown that giving older adults dietary advice and protein rich food products increased their dietary protein intake over 4 weeks, and most reported that they would continue following the advice on cessation of the study ( 19 ).…”
Section: Discussionmentioning
confidence: 99%